Variation as Christian identity marker in Egypt: A sociolinguistic study - Mahfouz, Adel Refaat (Research Journal in Advanced Humanities, 2024)
This study explores how variation marks the religious identity of the Egyptian Christians and helps in describing the present sociolinguistic landscape in Egypt. Data for this study has been collected from Christian friends, students, and neighbors as well as Christian T.V. programs and videos. Data has shown significant lexical and phonological differences in expressing common religious concepts, ritual expressions, and names. These differences, which depend mainly on synonyms, paraphrasing, loanwords, and pronunciation, constitute a shibboleth in Egypt. The study has revealed that not only is variation regional or social, but religious as well. Moreover, the colloquial lexis and non-standard speech forms that Christians use contradict Ferguson’s claim that the highly codified variety of diglossic languages is always used in giving sermons.  Although the variation is not that substantiative and does not impede understanding, the study has pointed out that there is a religious-based dialect differentiation in Egypt and the Egyptian Christians could be classified as bidialectal to some extent. The ultimate goal of this variation is to mark themselves as a different religious group in an Islamic society. The plethora of the Arabic lexis and expressions and the diglossic nature of Arabic enabled the Egyptian Christians to easily communicate with Muslims and simultaneously preserve their socio-religious identity.